Synthesis and in vitro human skin penetration of oligo- and polymeric ethylene glycol carbonates of zidovudine and stavudine - N'Da, David D.; Breytenbach, Jaco C.; Breytenbach, J Wilma (Arzneimittelforschung, 2010)
In continuation of studies focusing on the transdermal delivery of antiretroviral (ARV) drugs, the skin permeation ability of synthesized homologous series of both oligomeric and polymeric ethylene glycol (PEG) carbonates of zidovudine (3'-azido-3'-deoxythymidine, AZT, CAS 30516-87-1) and stavudine (2',3'-dideoxy-2',3'-didehydrothymine, d4T, CAS 3056-17-5) was evaluated in vitro through excised human skin in phosphate buffered solution (PBS) (0.01 M, pH 7.4) at 37°C by using Franz cell diffusion methodology. The results revealed that all the derivatives permeated the skin regardless of the series. However, the derivative having three ethylene glycol repeating units was the most effective permeant in each series. The skin permeation rates of zidovudine and stavudine were enhanced by factors in the 2-4, and 1-3 range through these carbonates, respectively.
Keywords: Antiretroviral drugs; Ethylene glycol; Ethylene oxide; Poly(ethylene glycol); Stavudine; Transdermal penetration; Zidovudine